Intercultural Education as a teaching innovation strategy in early Childhood Education - Aparicio Gervás, Jesús Mª; León Guerrero, Mª Montserrat (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The 2030 Agenda for Sustainable Development promotes an inclusive society. That is why we must start this process of intercultural coexistence from the Early Childhood Education. Through the central axis of the children´s story and using music as a motivating didactic resource, we will support the teaching action on three categorical axes: communication, image and sound. Methodologically, it is proposed from a qualitative and quantitative perspective, through the ethnographic method. The context is limited to an educational center with a vulnerable student body. The results have made it possible to overcome prejudices and stereotypes and build spaces for school inclusion.